2014
DOI: 10.1017/s0007114514002335
|View full text |Cite
|
Sign up to set email alerts
|

Style over substance: what can parenting styles tell us about ownership styles and obesity in companion animals?

Abstract: Obesity is a major medical concern in human subjects, and most concerning is the rapid recent increase in childhood obesity. Children are more likely to be obese if their parents are obese, an effect that is mediated both by genetics and environment, most notably parental influence. Four major parenting styles have been recognised: authoritative; authoritarian; indulgent; uninvolved. Too much parental control, as with the authoritarian style, is associated with a higher weight status in children. Conversely, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 63 publications
1
32
0
1
Order By: Relevance
“…making high demands on their children whilst showing little responsiveness to their opinions or wishes) are more likely to be overweight that those who show other styles ( 14 , 15 ) . There are many parallels between how parents care for children and how owners care for their dogs, and a recent review considered how pet ownership styles could be mapped to parenting styles ( 16 ) . If dog-ownership styles exist that are similar to the indulgent and authoritarian parent styles, then similar predispositions might exist for canine obesity.…”
Section: Discussionmentioning
confidence: 99%
“…making high demands on their children whilst showing little responsiveness to their opinions or wishes) are more likely to be overweight that those who show other styles ( 14 , 15 ) . There are many parallels between how parents care for children and how owners care for their dogs, and a recent review considered how pet ownership styles could be mapped to parenting styles ( 16 ) . If dog-ownership styles exist that are similar to the indulgent and authoritarian parent styles, then similar predispositions might exist for canine obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the term was further extended into contexts involving humans and objects, places and non-human animals [28,29]. It was previously suggested that humans can form an attachment to their dogs [30] and that this relationship is comparable to the one between a parent and a child [31], as human behavior towards dogs and children tends to be similar [32,33]. The attachment between two individuals can be secure, defined by comfort with intimacy and trust, or insecure.…”
Section: Introductionmentioning
confidence: 99%
“…At a behavioral level, humans tend to address and handle dogs and children in a similar way (Mitchell, 2001; Prato-Previde et al, 2006; German, 2015). Therefore, based on the attitudes of dog owners it can be assumed that the caretaking behavior of dog owners is similar to human parenting behavior.…”
Section: Introductionmentioning
confidence: 99%